Eksistensi Pendidikan Pesantren : Kritik Terhadap Kapitalisasi Pendidikan - Miftachul Ulum (TA'LIM : Jurnal Studi Pendidikan Islam, 2018)
Pesantren develops with an encompassing tradition which is supported by the presence of kiai as the guardian of wholeness and consistency of its establishment, character and ideology of kiai together with institutional pesantren. The existence of pesantren in the development of education is still well preserved, without much dependent on helping to improve the consistency of education. There are many interesting things from pesantren and it is not found in other institutions that are the standard subjects that are textualized in the salaf (classical) or yellow book. Pesantren that provide education during difficult times, the struggle against colonial and is a center of study that still survive to the present. The existence of pesantren in conducting education and character formation has been tested, so that many national figures are born through education in pesantren. But along with the global world, the realm of education has also changed, from the oriented to prepare human resources as part of strengthening the faith to the Almighty, turning to materialistic life. The liberal-capitalistic educational system is the whole form of educational management that serves as a means to gain only financial gain, which ignores the importance of education for every child. However, it is clear that the presence of pesantren makes one momentum remain its existence in the development of education that always put forward on the goal of education that haqiqi always based syiar Islam.